Process of Proving the Crime of Sexual Abuse against Underage Child Victims in the Gorontalo City Area - Mangati, Mursid; Insani, Nur; Nusa, Apriyanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The evidentiary process is the judge's consideration in determining whether a defendant is proven to have committed a criminal act or not. One of the evidentiary processes is listening to witness statements, defendant statements and letters. The research method used in this writing is normative juridical, with descriptive research specifications. This research uses secondary data obtained through literature and described systematically. Based on the results of research in Decision Number 52/Pid.Sus/2024/PN.GTO, the evidence in the crime of child molestation in this case does not fulfill the elements of proof contained in Article 183 of the Criminal Procedure Code. Witness statements, letters in the form of Visum Et Repertum are valid evidence and have also taken into account the statement of the defendant who does not admit his actions so that the judge is confident that the defendant is not the perpetrator of a crime and the panel of judges also considers the matters that decide the case independently of demands from the Public Prosecutor who charged